High-fluidity corrosion-resistant aluminum alloy material for laser cladding as well as preparation and application of high-fluidity corrosion-resistant aluminum alloy material

By reinstalizing a variety of metal elements and adding rare earth oxides and titanium carbide doped Ti3+, the laser melting material has poor liquidity and uneven performance, and aluminum alloy materials with high liquidity and uniform performance are realized.

CN119351833AInactive Publication Date: 2025-01-24BEIJING SURYEE SCI & TECH CO LTD

Patent Information

Application Number
CN202411933270.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The current laser cladding materials have poor fluidity, which leads to high difficulty in bonding with the substrate, and uneven performances such as wear resistance, high temperature resistance, corrosion resistance, etc.

Method used

Through metallic elements such as nickel, molybdenum, cobalt, silicon, and adding titanium oxides and doped ti3+as a functional additive, the liquidity and performance of aluminum alloy are improved.

Benefits of technology

The fluidity and performance of aluminum alloys are significantly improved, and the coating formed has uniform wear resistance, high temperature resistance, corrosion resistance and oxidation resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum alloys, in particular to a high-fluidity corrosion-resistant aluminum alloy material for laser cladding as well as preparation and application of the high-fluidity corrosion-resistant aluminum alloy material. The material comprises the following components in percentage by mass: 3.12%-5.34% of nickel, 4.24%-6.76% of molybdenum, 6.54%-8.12% of cobalt, 10.45%-14.49% of silicon, 5.65%-8.45% of a functional additive, 1.25%-2.45% of cerium oxide, 3.46%-7.42% of yttrium oxide, 3.45%-7.58% of lanthanum oxide and the balance of aluminum, the functional additive is titanium carbide doped with Ti < 3 + >. The aluminum alloy material has high flowability during laser cladding and is well combined with a matrix, and related properties such as wear resistance, high temperature resistance, corrosion resistance and oxidation resistance of a coating formed by the aluminum alloy material are sufficiently uniform due to the high flowability of the aluminum alloy material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum alloys, and in particular relates to a high-fluidity, corrosion-resistant aluminum alloy material for laser cladding, and a preparation method and application thereof. Background Art

[0002] Laser cladding refers to placing the selected coating material on the surface of the coated substrate in different filling methods (synchronous powder feeding or pre-placed powder), and then irradiating it with a high-energy laser beam to melt the coating material and a thin layer on the surface of the substrate material at the same time, and then quickly solidify to form a surface coating with extremely low dilution and metallurgical bonding with the substrate. Commonly used materials for laser cladding include nickel-based alloys, cobalt-based alloys, iron-based alloy tungsten carbide composite materials, ceramic materials, etc., but the above materials have poor fluidity and are difficult to bond with the substrate.

[0003] For example, CN114959686A discloses a laser cladding powder and a method for laser cladding on the surface of an aluminum alloy, which belongs to the field of laser cladding technology. The laser cladding powder includes: 8-20wt% nickel-based alloy powder, 5-12wt% tungsten carbide powder and 70-80wt% copper powder. The nickel-based alloy powder includes 0.6-1.0wt% C, 14-17wt% Cr, 2.5-4.5wt% B, 3-4.5wt% Si and the remainder Ni. This application only uses rare earth elements to eliminate the brittleness of the nickel base, and its corrosion resistance, but the corrosion resistance of each part is quite different, and the fluidity still needs to be further improved.

[0004] For example, CN115094417A discloses a highly wear-resistant nickel-based laser cladding powder for a titanium alloy surface and a laser cladding method thereof. The laser cladding method comprises: S1, grinding the surface of the laser cladding sample with sandpaper to remove surface oxide scale and stains, cleaning the surface of the sample with anhydrous ethanol and acetone, and drying for standby use; S2, placing the dried sample in step 1 into a heater for preheating; S3, placing the dried laser cladding powder into a powder feeder, and continuously feeding powder using a coaxial powder feeding system to complete laser cladding; wherein the laser cladding powder is made of the following materials in weight percentage: Cr 16%-17%, Fe 3.5%-4.0%, C 0.5%-1.0%, B 2.8%-3.2%, Si 4.0%-4.5%, Cu 3.0%-3.5%, Mo 2.8%-3.2%, O<0.1%, the rest is nickel and unavoidable impurities; S4, the laser cladding sample was sanded and polished with sandpaper, and hardness and wear resistance tests were performed. This application improves its wear resistance by adding Cu and Mo elements, but the wear resistance of each part varies greatly, and its fluidity still needs to be further improved.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a high-fluidity, corrosion-resistant aluminum alloy material for laser cladding and its preparation and application. The aluminum alloy material has high fluidity during laser cladding and combines well with a substrate. Its high fluidity makes the relevant properties of the coating formed by it, such as wear resistance, high temperature resistance, corrosion resistance, and oxidation resistance, sufficiently uniform.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: In a first aspect, an embodiment of the present invention provides a high-fluidity, corrosion-resistant aluminum alloy material for laser cladding, comprising the following components by mass ratio: 3.12-5.34% nickel, 4.24-6.76% molybdenum, 6.54-8.12% cobalt, 10.45-14.49% silicon, 5.65-8.45% functional additives, 1.25-2.45% cerium oxide, 3.46-7.42% yttrium oxide, 3.45-7.58% lanthanum oxide, and the balance aluminum; The functional additive is doped with Ti 3+ of titanium carbide.

[0008] The present invention effectively improves the fluidity of the aluminum alloy and enhances the wear resistance, high temperature resistance, corrosion resistance, oxidation resistance and other properties of the aluminum alloy by compounding a variety of metal elements and adding rare earth oxides.

[0009] Specifically, the compounded rare earth oxides of the present invention can serve as the core of heterogeneous nucleation during the laser cladding process of aluminum alloy, so that the aluminum alloy forms more fine and uniform grains during the solidification process, and can react with the impurity elements in the aluminum alloy to generate fine and dispersed compounds, thereby reducing the adverse effects of the impurity elements on the fluidity of the aluminum alloy; in addition, during laser cladding, rare earth oxides such as cerium oxide, yttrium oxide, and lanthanum oxide have high chemical activity and can form a relatively stable oxide film on the surface of the aluminum alloy liquid. This oxide film can reduce the surface tension between the aluminum alloy liquid and the casting mold, making it easier for the aluminum alloy liquid to spread and fill in the casting mold, thereby improving its fluidity; and the compounded rare earth oxides of the present invention can widen the solidification temperature range of the aluminum alloy. In a wider solidification temperature range, the alloy liquid remains in liquid for a relatively longer time, which is conducive to its flow in the matrix, thereby improving the fluidity of the alloy, and the addition of the compounded rare earth oxides of the present invention can change the liquid structure of the aluminum alloy, weaken the interaction between atoms or molecules in the alloy liquid, thereby reducing the viscosity of the alloy liquid. After the viscosity is reduced, the alloy liquid is easier to flow under the action of gravity or external force; it should also be noted that impurities such as oxygen and sulfur are inevitably generated during the laser cladding process, and the rare earth oxides compounded in the present invention have certain deoxidation and desulfurization capabilities, which can remove harmful gases and impurities such as oxygen and sulfur in the aluminum alloy. This further improves the purity of the aluminum alloy, reduces its internal defects and inclusions, improves the continuity and uniformity of the liquid alloy, and helps to improve the fluidity of the alloy.

[0010] In addition, the rare earth oxides compounded in the present invention have good synergistic effects with each metal element, so that the wear resistance, high temperature resistance, corrosion resistance, oxidation resistance and other properties of the aluminum alloy are greatly improved. Among them, cerium oxide has the effect of refining grains for elements such as molybdenum. When cerium oxide is added, the grains of molybdenum, nickel and cobalt can be significantly refined, and the wear resistance, high temperature resistance, corrosion resistance and other properties of the alloy formed can be improved. Yttrium oxide has good chemical stability and thermal stability. Adding yttrium oxide can improve the high temperature resistance, oxidation resistance and mechanical strength of aluminum alloys. It mainly improves the creep resistance of aluminum alloys and refines the grains of metal elements, thereby effectively improving its high temperature resistance. Lanthanum oxide can refine the grains of metal elements, improve the strength and toughness of aluminum alloys, further improve the wear resistance and oxidation resistance of aluminum alloys, and lanthanum oxide can also increase the recrystallization temperature of the metal added in this application, inhibit grain growth, thereby improving the high temperature resistance of aluminum alloys.

[0011] In addition, the present application also adds self-made functional additives. The functional additives added in the present invention can have a synergistic effect with the rare earth oxide compounded in the present invention, such as refining grains, improving the fluidity of aluminum alloys, and improving oxidation resistance. More importantly, in aluminum alloys, titanium carbide, as a hard dispersed phase, can hinder dislocation movement, thereby improving the strength of the material, while rare earth oxides can make the distribution of titanium carbide in the alloy more uniform by refining grains and changing the microstructure of the alloy. This evenly distributed titanium carbide can more effectively play the role of dispersion strengthening, while rare earth oxides can also enhance the bonding strength of the alloy matrix to a certain extent, further improving the strength of the material. In addition, the self-made titanium carbide doped with Ti in the present application 3+ The titanium carbide further enhances the above properties.

[0012] In a preferred embodiment, the preparation method of the functional additive comprises the following steps: Titanium carbide and zirconium oxide are mixed in a solvent, ball-milled at 2000-3000 r / min for 2-4 hours, filtered and dried to obtain a functional additive.

[0013] In a preferred embodiment, the average particle size of the titanium carbide is 50-100 nm.

[0014] In a preferred embodiment, the mass ratio of titanium carbide, zirconium oxide and solvent is 1: (9000-12000): (18000-24000).

[0015] In a preferred embodiment, the particle size of the zirconium oxide is 0.03-0.5 mm; In a preferred embodiment, the solvent is an ethanol solution containing titanium trichloride, and the concentration of titanium trichloride is 1-2 g / L.

[0016] Since the compatibility of titanium carbide and aluminum alloy itself needs to be improved, the present invention enhances the compatibility of aluminum alloy and titanium carbide by introducing trivalent titanium particles into titanium carbide, and further enhances the fluidity, mechanical properties, corrosion resistance, etc. of the aluminum alloy.

[0017] This is mainly because the introduction of trivalent titanium ions will trigger some special chemical reactions at the interface between titanium carbide and aluminum alloy. Trivalent titanium ions have certain chemical activity and can react chemically with elements in aluminum alloys, such as aluminum and nickel, to form chemical bonds or interface phases with strong binding force. This chemical bonding can significantly enhance the bonding strength between titanium carbide and aluminum alloy, make the interface between the two more stable, and reduce the possibility of interface separation under conditions such as force or high temperature. At the same time, the presence of trivalent titanium ions may change the chemical reaction path at the interface and inhibit the occurrence of some harmful reactions that may weaken the interface. In the absence of trivalent titanium ions, some elements in the aluminum alloy may react with impurities or oxides on the surface of titanium carbide to generate some brittle phases or low melting point phases, which will reduce the bonding strength of the interface and the overall performance of the material. The introduction of trivalent titanium ions can preferentially react with these impurities or oxides, prevent harmful reactions from occurring, and thus improve compatibility. In addition, both trivalent titanium ions and titanium carbide have the effect of refining alloy grains. Trivalent titanium ions can serve as the core of heterogeneous nucleation, increase the nucleation sites during the solidification of aluminum alloys, and thus refine the grains. Titanium carbide itself can also play a similar role in heterogeneous nucleation during the solidification process of aluminum alloys. When the two work together, they can produce a synergistic effect, making the grains of aluminum alloys more significantly refined. The refined grain structure can improve the strength, toughness, and corrosion resistance of aluminum alloys, and also help improve the processing performance and surface quality of the material; more importantly, the introduction of trivalent titanium ions can improve the hardness and strength of titanium carbide, reduce the gap in mechanical properties between it and aluminum alloys, and thus improve the compatibility of the two. And titanium carbide containing trivalent titanium ions as a reinforcing phase can significantly improve the overall strength and hardness of aluminum alloys, while maintaining the toughness of the aluminum alloy matrix, so that the material has better comprehensive mechanical properties.

[0018] In a second aspect, an embodiment of the present invention provides a method for preparing the above-mentioned high-fluidity corrosion-resistant aluminum alloy material for laser cladding, comprising the following steps: Under inert gas, pure nickel powder, pure molybdenum powder, pure cobalt powder, pure silicon powder and pure aluminum powder are mixed, ball milled once to obtain a primary mixture, the primary mixture is mixed evenly with cerium oxide, yttrium oxide and lanthanum oxide, ball milled twice to obtain a secondary mixture, the secondary mixture is mixed evenly with functional additives, and ball milled three times to obtain the secondary mixture aluminum alloy material for laser cladding.

[0019] In a preferred embodiment, the average particle size of the pure nickel powder is 15-100 μm.

[0020] In a preferred embodiment, the average particle size of the pure molybdenum powder is 15-100 μm.

[0021] In a preferred embodiment, the average particle size of the pure cobalt powder is 15-100 μm.

[0022] In a preferred embodiment, the average particle size of the pure silicon powder is 15-100 μm.

[0023] In a preferred embodiment, the average particle size of the pure aluminum powder is 15-100 μm.

[0024] In a preferred embodiment, the average particle size of the cerium oxide is 15-100 μm.

[0025] In a preferred embodiment, the average particle size of the yttrium oxide is 15-100 μm.

[0026] In a preferred embodiment, the average particle size of the lanthanum oxide is 15-100 μm.

[0027] In a preferred embodiment, the specific conditions of the first ball milling are: 200-400 r / min ball milling for 3-6 hours.

[0028] In a preferred embodiment, the specific conditions of the secondary ball milling are: ball milling at 200-400 r / min for 2-4 h.

[0029] In a preferred embodiment, the specific conditions of the three ball millings are: 200-400 r / min ball milling for 1-2 h.

[0030] In a third aspect, an embodiment of the present invention provides an application of the above-mentioned high-fluidity, corrosion-resistant aluminum alloy material for laser cladding in laser cladding.

[0031] In a preferred embodiment, the substrate for laser cladding in the application is an aluminum alloy or pure aluminum.

[0032] The present invention is particularly preferably used for surface coating of aluminum alloys. Since aluminum accounts for a high proportion in the composite material of the present invention, when used as a laser cladding material with aluminum alloy as a substrate, it has good compatibility with the substrate and is easier to exert its performance.

[0033] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The elements such as nickel, molybdenum, cobalt, silicon, etc. added to the aluminum alloy of the present invention can effectively improve the mechanical properties of the aluminum alloy, improve the casting performance of the aluminum alloy, enhance the corrosion resistance of the aluminum alloy, and improve the heat resistance of the aluminum alloy.

[0034] 2. The present invention effectively improves the fluidity of aluminum alloy and improves the wear resistance, high temperature resistance, corrosion resistance, oxidation resistance and other properties of aluminum alloy by compounding multiple metal elements and adding rare earth oxides.

[0035] 3. The functional additives added in the present invention can have a synergistic effect with the rare earth oxide compounded in the present invention in terms of grain refinement, improvement of aluminum alloy fluidity, and improvement of oxidation resistance. More importantly, in aluminum alloys, titanium carbide, as a hard dispersed phase, can hinder dislocation movement, thereby improving the strength of the material, while rare earth oxides can make the distribution of titanium carbide in the alloy more uniform by refining grains and changing the microstructure of the alloy.

[0036] 4. Since the compatibility of titanium carbide and aluminum alloy itself needs to be improved, the present invention enhances the compatibility of aluminum alloy and titanium carbide by introducing trivalent titanium particles into titanium carbide, and further enhances the fluidity, mechanical properties, corrosion resistance, etc. of the aluminum alloy. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available.

[0039] Example 1 This embodiment provides a method for preparing the above-mentioned high-fluidity corrosion-resistant aluminum alloy material for laser cladding, comprising the following steps: Under nitrogen atmosphere, 3.58% pure nickel powder with an average particle size of 50 μm, 4.96% pure molybdenum powder with an average particle size of 50 μm, 7.56% pure cobalt powder with an average particle size of 50 μm, 12.12% pure silicon powder with an average particle size of 50 μm and 51.34% aluminum powder with an average particle size of 50 μm were mixed, by mass, and ball milled at 300 r / min for 4 h to obtain a primary mixture, the primary mixture was mixed with 1.96% cerium oxide with an average particle size of 50 μm, 5.68% yttrium oxide with an average particle size of 50 μm, and 5.96% lanthanum oxide with an average particle size of 50 μm, and ball milled at 300 r / min for 3 h to obtain a secondary mixture, the secondary mixture was mixed with 6.84% functional additives, and ball milled at 300 r / min for 1.5 h to obtain the secondary mixture aluminum alloy material for laser cladding.

[0040] The preparation method of the functional additive comprises the following steps: Titanium carbide with an average particle size of 70 nm and zirconium oxide are mixed in an ethanol solution of titanium trichloride, ball-milled at 2500 r / min for 2-4 hours, filtered and dried to obtain a functional additive, wherein the mass ratio of titanium carbide, zirconium oxide and ethanol solution of titanium trichloride is 1:10000:20000, the particle sizes of zirconium oxide are 0.03, 0.1, 0.3 and 0.5 mm, the zirconium oxide of each particle size is one quarter of its total mass, and the concentration of titanium trichloride is 1.5 g / L.

[0041] Example 2 This embodiment provides a method for preparing the above-mentioned high-fluidity corrosion-resistant aluminum alloy material for laser cladding, comprising the following steps: Under nitrogen atmosphere, 4.58% pure nickel powder with an average particle size of 50 μm, 6.44% pure molybdenum powder with an average particle size of 50 μm, 8.01% pure cobalt powder with an average particle size of 50 μm, 13.23% pure silicon powder with an average particle size of 50 μm and 46.3% aluminum powder with an average particle size of 50 μm were mixed by mass, and ball milled at 300 r / min for 4 h to obtain a primary mixture, the primary mixture was mixed with 1.96% cerium oxide with an average particle size of 50 μm, 5.68% yttrium oxide with an average particle size of 50 μm, and 5.96% lanthanum oxide with an average particle size of 50 μm, and ball milled at 300 r / min for 3 h to obtain a secondary mixture, the secondary mixture was mixed with 7.84% functional additives, and ball milled at 300 r / min for 1.5 h to obtain the secondary mixture aluminum alloy material for laser cladding.

[0042] The preparation method of the functional additive comprises the following steps: Titanium carbide with an average particle size of 70 nm and zirconium oxide are mixed in an ethanol solution of titanium trichloride, ball-milled at 2500 r / min for 2-4 hours, filtered and dried to obtain a functional additive, wherein the mass ratio of titanium carbide, zirconium oxide and ethanol solution of titanium trichloride is 1:10000:20000, the particle sizes of zirconium oxide are 0.03, 0.1, 0.3 and 0.5 mm, the zirconium oxide of each particle size is one quarter of its total mass, and the concentration of titanium trichloride is 1.5 g / L.

[0043] Comparative Example 1 The difference between this comparative example and Example 1 is that the functional additive is changed to titanium carbide with an average particle size of 70 nm.

[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that cerium oxide is not added, and the mass proportion of yttrium oxide is changed to 6.66%, and the mass proportion of lanthanum oxide is changed to 6.94%.

[0045] Comparative Example 3 The difference between this comparative example and Example 1 is that yttrium oxide is not added, and the mass proportion of cerium oxide is changed to 4.8%, and the mass proportion of lanthanum oxide is changed to 8.8%.

[0046] Comparative Example 4 The difference between this comparative example and Example 1 is that lanthanum oxide is not added, and the mass proportion of cerium oxide is changed to 4.94%, and the mass proportion of yttrium oxide is changed to 8.66%.

[0047] Comparative Example 5 The difference between this comparative example and Example 1 is that cerium oxide, yttrium oxide and lanthanum oxide are not added, and the mass proportion of pure aluminum powder is changed to 64.94%.

[0048] Comparative Example 6 The difference between this comparative example and Example 1 is that no functional additive is added, and the mass proportion of pure aluminum powder is changed to 58.18%.

[0049] Comparative Example 7 The difference between this comparative example and Example 1 is that the average particle size of pure nickel powder, pure molybdenum powder, pure cobalt powder, pure silicon powder and pure aluminum powder is changed to 120 μm.

[0050] Performance Testing 100cm*50cm*100cm pure aluminum was selected as the substrate, and the materials obtained in the embodiment and the comparative example were melted by laser cladding technology to form a coating on the surface of the substrate, and the coating thickness was 0.5cm.

[0051] 1. Refer to YS / T 420-2023 to test the Vickers hardness of the coating. The test results are shown in Table 1.

[0052] 2. The anti-wear test was carried out using the UMT-3 controlled environment friction and wear testing machine: pressure 100N, speed 300r / min, time 90min, and the wear amount was measured. The test results are shown in Table 1.

[0053] 3. Using a φ19 carbide pick head, the number of cracks on the coating was tested under a 120MPa impact force. The test results are shown in Table 1.

[0054] 4. The objects obtained after laser cladding of pure aluminum in the embodiment and the comparative example were sent into a muffle furnace for heating at a temperature of 1000°C and a heating time of 10 minutes. Then, they were steadily removed from the furnace for air cooling, and the natural droop of the free end of the sample, i.e., the droop value, was measured with a vernier caliper. The test results are shown in Table 1.

[0055] 5. Test 1, test 2, test 3, test 4, and test 5 were performed at intervals of 20 cm in the length direction. The Vickers hardness of the coating was tested according to YS / T 420-2023. The test results are shown in Table 2. The wear resistance test was performed using a UMT-3 controlled environment friction and wear tester: pressure 100N, speed 300r / min, time 90min, and the wear amount of each test part was measured. The test results are shown in Table 3. Table 1 Performance test results

[0056] Table 2 Performance test results

[0057] Table 3 Performance test results

[0058] From the above performance test results, it can be seen that the wear resistance, high temperature resistance, corrosion resistance and oxidation resistance of Examples 1-2 are good, especially due to their good fluidity, the mechanical properties of the coating formed are further uniform, especially the comprehensive performance of Example 2 is the most outstanding, which is mainly because the rare earth oxides and homemade functional additives of the present invention synergistically improve the fluidity and mechanical properties of the material. The comparative example is significantly worse than the example in the corresponding performance test because it does not adopt the necessary technical solution, which better proves the irreplaceable nature of the specific technical solution of this application in achieving technical effects and solving technical problems.

[0059] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-fluidity, corrosion-resistant aluminum alloy material for laser cladding, characterized in that: The invention comprises the following components in mass ratio: 3.12-5.34% nickel, 4.24-6.76% molybdenum, 6.54-8.12% cobalt, 10.45-14.49% silicon, 5.65-8.45% functional additive, 1.25-2.45% cerium oxide, 3.46-7.42% yttrium oxide, 3.45-7.58% lanthanum oxide, and the balance aluminum; The functional additive is doped with Ti 3+ of titanium carbide.

2. The high fluidity, corrosion-resistant aluminum alloy material for laser cladding according to claim 1, characterized in that: The preparation method of the functional additive comprises the following steps: Titanium carbide and zirconium oxide are mixed in a solvent, ball-milled at 2000-3000 r / min for 2-4 hours, filtered and dried to obtain a functional additive.

3. The high fluidity, corrosion-resistant aluminum alloy material for laser cladding according to claim 2, characterized in that: The average particle size of the titanium carbide is 50-100 nm.

4. The high fluidity, corrosion-resistant aluminum alloy material for laser cladding according to claim 2, characterized in that: The mass ratio of titanium carbide, zirconium oxide and solvent is 1:(9000-12000):(18000-24000).

5. The high fluidity, corrosion-resistant aluminum alloy material for laser cladding according to claim 2, characterized in that: The particle size of the zirconium oxide is 0.03-0.5 mm.

6. The high fluidity, corrosion-resistant aluminum alloy material for laser cladding according to claim 2, characterized in that: The solvent is an ethanol solution in which titanium trichloride is dissolved, and the concentration of the titanium trichloride is 1-2 g / L.

7. A method for preparing a high-fluidity, corrosion-resistant aluminum alloy material for laser cladding as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: Under inert gas, pure nickel powder, pure molybdenum powder, pure cobalt powder, pure silicon powder and pure aluminum powder are mixed, ball milled once to obtain a primary mixture, the primary mixture is mixed evenly with cerium oxide, yttrium oxide and lanthanum oxide, ball milled twice to obtain a secondary mixture, the secondary mixture is mixed evenly with functional additives, and ball milled three times to obtain the secondary mixture aluminum alloy material for laser cladding.

8. The method for preparing a high-fluidity, corrosion-resistant aluminum alloy material for laser cladding according to claim 7, characterized in that: The average particle size of the pure cobalt powder is 15-100 μm; And / or, the average particle size of the pure silicon powder is 15-100 μm; And / or, the average particle size of the pure aluminum powder is 15-100 μm; And / or, the average particle size of the cerium oxide is 15-100 μm; And / or, the average particle size of the yttrium oxide is 15-100 μm; And / or, the average particle size of the lanthanum oxide is 15-100 μm.

9. The method for preparing a high-fluidity, corrosion-resistant aluminum alloy material for laser cladding according to claim 7, characterized in that: The specific conditions of the first ball milling are: 200-400r / min ball milling for 3-6h; And / or, the specific conditions of the secondary ball milling are: ball milling at 200-400 r / min for 2-4 hours; And / or, the specific conditions of the three ball millings are: ball milling at 200-400 r / min for 1-2 h.

10. Use of the high fluidity, corrosion-resistant aluminum alloy material for laser cladding as claimed in any one of claims 1 to 6 in laser cladding.

Citation Information

Patent Citations

  • Laser cladding powder and method for laser cladding on surface of aluminum alloy

    CN114959686A

  • Titanium alloy surface high-wear-resistance nickel-based laser cladding powder and laser cladding method thereof

    CN115094417A

  • Method for producing Ni-Al bimetal composite material solid core wire material

    CN101413096A

  • Process for laser cladding of rare earth yttrium oxide, aluminum and iron-based alloy composite coating layer on surface of aluminum alloy

    CN104120425A

  • Preparation method of ceramic reinforced aluminum matrix composite wear-resistant coating, aluminum alloy material and train brake disc

    CN116180071A

Cited By

  • Corrosion-resistant and wear-resistant silicon bronze alloy material and preparation method thereof

    CN120006137A

  • High-performance and high-temperature-resistant aluminum alloy and preparation method thereof

    CN120099364A

  • A high-performance, high-temperature-resistant aluminum alloy and its preparation method

    CN120099364B

  • High-temperature-resistant and corrosion-resistant alloy material and preparation method thereof

    CN122189529A